IMPROVEMENT QUALITY MANAGEMENT OF EDUCATOR AND EDUCATIONAL STAFF IN THE IMPLEMENTATION OF CURRICULUM 2013 - Madjid, Abdul; Sonhadji, Ahmad; Imron, Ali; Arifin, Imron (IJRDO- Journal of Educational Research, 2017)
The purpose of this research is to find out how to improve the quality of education andeducation personnel on the implementation of Curriculum 2013 (in the SMAN 3, MAN 3 and SMKN4 Malang), both in planning, organizing, implementation, and monitoring and evaluation aspects.The approach used in this research is qualitative research method, which aims to comprehendphenomenon or social phenomenon comprehensively and contextually by describing empiricalreality about management of quality improvement of education and educational staff on theimplementation of Curriculum 2013 in SMA/MA/SMK Negeri Malang. Data collection techniquesare through indepth interview mechanism, participatory observation and documentation analysis aswell as multicasus data analysis, in individual cases and/or crosscases analysis cases. The studyfound that the management of quality improvement of educators and educational personnel in theimplementation of Curriculum 2013 in SMA/MA/SMK Negeri Malang, including planning,organizing, implementation, monitoring and evaluation in the field of (a) training; (b) development;and (c) mentoring.